Efficacy and safety of maintenance intravenous immunoglobulin in generalized myasthenia gravis patients with acetylcholine receptor antibodies: A multicenter, double-blind, placebo-controlled trial - Bril, Vera; Berkowicz, Tomasz; Szczudlik, Andrzej; Nicolle, Michael W; Bednarik, Josef; Hon, Petr; Vaitkus, Antanas; Vu, Tuan; Rozsa, Csilla; Magnus, Tim; Panczel, Gyula; Toomsoo, Toomas; et al. (Muscle & nerve, 2025)
INTRODUCTION/AIMS: Prospective, randomized, controlled trials of intravenous immunoglobulin (IVIG) maintenance therapy in myasthenia gravis (MG) are lacking. In this trial, we evaluated the safety and efficacy of caprylate/chromatography-purified IVIG; (IGIV-C) in patients with generalized MG undergoing standard care. METHODS: Sixty-two patients enrolled in this phase 2, multicenter, international, randomized trial (1:1 IGIV-C [2 g/kg loading dose; 1 g/kg every 3 weeks through week 21] or placebo). Efficacy was assessed by changes in Quantitative MG (QMG) score at week 24 versus baseline (primary endpoint) and percentage of patients with clinical improvement in QMG, MG Composite (MGC), and MG-Activities of Daily Living (MG-ADL) scores (secondary endpoints). Safety assessments reported all adverse events (AEs). RESULTS: The change in QMG at 24 weeks was -5.1 for IGIV-C and -3.1 for placebo (p = .187). Seventy percent of patients in the IGIV-C group had improvement in MG-ADL (≥2-point decrease) versus 40.6% in the placebo group (p = .025). Patients showing clinical improvement in QMG and MGC (≥3-point decrease) were 70.0% for IGIV-C versus 59.4% for placebo (p = .442) and 60.0% for IGIV-C versus 53.1% for placebo (p = .610). IGIV-C was well tolerated; serious AEs were similar between arms. Three of four MG exacerbations requiring hospitalizations occurred in the IGIV-C arm with one death. DISCUSSION: Several efficacy parameters showed numerical results greater than those seen in the placebo group. This was a small study and may have been underpowered to see significant differences. Additional studies may be warranted to fully determine the efficacy of IVIG maintenance therapy in MG.
Keywords: dospělí; intravenózní imunoglobuliny; Female; autoprotilátky; Adult; výsledek terapie; myasthenia gravis; ženské pohlaví; receptory cholinergní; imunologické faktory; lidé; dvojitá slepá metoda; Immunoglobulins, Intravenous; Activities of Daily Living; neuromuscular disease; Treatment Outcome; Receptors, Cholinergic; Myasthenia Gravis; činnosti denního života; prospektivní studie; Double-Blind Method; Male; Immunologic Factors; Aged; Autoantibodies; Prospective Studies; intravenous immunoglobulin; lidé středního věku; senioři; mužské pohlaví; autoimmune disease; Middle Aged; Humans